Аналіз первинної і вторинної структури РН домену білка Bcr - Мірошниченко, Д.О.; Малюта, О.В.; Ложко, Д.М.; Телегеєв, Г.Д.; Малюта, С.С. (Видавничий дім "Академперіодика" НАН України, 2007)
The primary structure of Bcr PH domain is analyzed by using biological databank. To obtain the experimental secondary structure content of the recombinant PH protein, CD spectra were measured at 200–240 nm. The data observed correlate to ones for PH domains with determined structure.